2017
DOI: 10.1016/j.proci.2016.06.140
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of turbulent flame propagation in equivalence ratio-stratified flow

Abstract: Effects of equivalence ratio stratification on turbulent combustion processes are investigated using Direct Numerical Simulation. The simulation results are analysed in terms of flame surface area and the burning intensity. The local effects of stratification are then investigated further by examining statistics of the displacement speed conditioned on the flame-normal equivalence ratio gradient. The local burning intensity is found to depend on the orientation of the stratification with respect to the flame f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The unit-problem DNS, although shown in Figure 5 with dashed lines, was not included in the above discussion. For engine combustion, the limits between unit problems and process level are continuous; for instance, the DNS of a stratified flame 126 could be attributed to both levels, for example, if the stratification in the DNS is close to a mixture condition identified in step 1. A review of available DNS datasets, mostly at the unit-problem level, can be found in Barlow et al 108 Although the discussion is deliberately kept generic here, it is clear that the approach described above ensures that the process initially starts on the system level (step 1), then consecutively steps down the pyramid (steps 2-6) before it finally returns to the system level (step 7; see Figures 4 and 5).…”
Section: -125mentioning
confidence: 99%
See 1 more Smart Citation
“…The unit-problem DNS, although shown in Figure 5 with dashed lines, was not included in the above discussion. For engine combustion, the limits between unit problems and process level are continuous; for instance, the DNS of a stratified flame 126 could be attributed to both levels, for example, if the stratification in the DNS is close to a mixture condition identified in step 1. A review of available DNS datasets, mostly at the unit-problem level, can be found in Barlow et al 108 Although the discussion is deliberately kept generic here, it is clear that the approach described above ensures that the process initially starts on the system level (step 1), then consecutively steps down the pyramid (steps 2-6) before it finally returns to the system level (step 7; see Figures 4 and 5).…”
Section: -125mentioning
confidence: 99%
“…The unit-problem DNS, although shown in Figure 5 with dashed lines, was not included in the above discussion. For engine combustion, the limits between unit problems and process level are continuous; for instance, the DNS of a stratified flame 126 could be attributed to both levels, for example, if the stratification in the DNS is close to a mixture condition identified in step 1. A review of available DNS datasets, mostly at the unit-problem level, can be found in Barlow et al 108…”
Section: Approach For Systematic Model Evaluation and Development Formentioning
confidence: 99%
“…But for some fuels with lower H/C ratio, the reduced level of key radicals consumed by combustion intermediate products might reduce fuel consumption speeds compared to homogeneous flame. Richardson 18 investigated the turbulent methane−air stratified flame propagation using direct numerical simulation. The effect of equivalence ratio stratification on flame behavior, which had been observed in laminar flame previously, was also found in turbulent combustion.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of partially premixed flames, it has been utilised to study the effect of mixture fraction gradients on flame propagation speed in turbulent mixing layers [35], droplet combustion [36], and slot-jet flames with varying equivalence ratio inlets [37]. Indeed, these studies have provided many useful insights for partially premixed flames but the joint behaviour of Z and c were not examined from a modelling perspective.…”
Section: Introductionmentioning
confidence: 99%